If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -1) = x(x + 1) Reorder the terms: x(-1 + x) = x(x + 1) (-1 * x + x * x) = x(x + 1) (-1x + x2) = x(x + 1) Reorder the terms: -1x + x2 = x(1 + x) -1x + x2 = (1 * x + x * x) -1x + x2 = (1x + x2) Add '-1x2' to each side of the equation. -1x + x2 + -1x2 = 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -1x + 0 = 1x + x2 + -1x2 -1x = 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -1x = 1x + 0 -1x = 1x Solving -1x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1x + -1x = 1x + -1x Combine like terms: -1x + -1x = -2x -2x = 1x + -1x Combine like terms: 1x + -1x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 60-8x=8x | | 11y-6y-13=55.90 | | 6-24x+36y=0 | | -25+3x=-2x | | 11x-9-5=10x-4+3x | | 4x+5x-42=70-5x | | 15x=4/10 | | (x-5)+17=-3 | | 2tsp=XmL | | 38-4x=12+9x | | 42-n=28 | | -11=3+7x | | b-3+4b=-7+4b | | 3/5+2x=2/5 | | 4(x+18)=-2(x-6) | | -11X+6Y=-13 | | 2w-15w-18=-83 | | 13y-10y=9 | | (2xy-y)(2xy-y)= | | 46q-34=54q-82 | | 1/4x+3=17 | | (n/8)-3=-11 | | -7(1+7r)-6=379 | | s^2+8s-9=0 | | 125m-75m+43875=46125-175m | | 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= |